2016
DOI: 10.1021/acs.joc.6b00049
|View full text |Cite
|
Sign up to set email alerts
|

Chiral N-Phosphonyl Imines for an Aza-Morita–Baylis–Hillman Reaction via Group-Assisted Purification (GAP) Chemistry

Abstract: Seventeen examples of aza-Morita-Baylis-Hillman (aza-MBH) adducts have been synthesized by reacting chiral N-phosphonyl imines with acrylonitrile in good to excellent yields (up to 96%) and high diastereoselectivity (up to 99:1 dr). The synthesis of these adducts followed the method of group-assisted purification (GAP) chemistry, in which the pure aza-MBH products were readily obtained by washing the crude products with cosolvents of hexane and ethyl acetate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…This indicated that 1a was converted to 2a in quantitative yield and that the current reaction system did not generate any organic waste. In addition, the present methodology fulfills the key criteria of group-assisted purification chemistry/technology, in which the products can be isolated conveniently by controlling solubility of desired products, thereby avoiding the chromatography step. A control experiment indicated that I 2 O 5 was essential for successful conversion (entry 13).…”
Section: Results and Discussionmentioning
confidence: 98%
“…This indicated that 1a was converted to 2a in quantitative yield and that the current reaction system did not generate any organic waste. In addition, the present methodology fulfills the key criteria of group-assisted purification chemistry/technology, in which the products can be isolated conveniently by controlling solubility of desired products, thereby avoiding the chromatography step. A control experiment indicated that I 2 O 5 was essential for successful conversion (entry 13).…”
Section: Results and Discussionmentioning
confidence: 98%
“…[ 45 ] It is noteworthy that the purification of desired product only needs to be carried out by washing with 95% EtOH solvent without traditional chromatography and recrystallization, which followed the group‐assisted purification (GAP) chemistry/technology. [ 46‐48 ] The formation of products 21 and 23 undergoes a very similar pathway including [2 + 2] cycloaddition, 1,6‐nucleophilic addition, ring opening of the cyclobutene and deprotonation/isomerization sequence (Scheme 7b).…”
Section: Synthesis Of Carbocyclesmentioning
confidence: 99%
“…34 Over the past decade, our group has developed Group-Assisted Purication (GAP) chemistry. [40][41][42][43][44] In essence, highly functionalized chiral N-phosphonyl/N-phosphinyl imines were a Mannich-type reaction, 45 aza-MBH reaction, 46 Strecker reaction, 43 Umpolung reaction, 47 and the synthesis of peptides 48 among others. Recently, our group discovered a novel form of chirality, multi-layer 3D chirality, via GAP chemistry in which restriction of the free rotation of intramolecular layers generates chirality.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it provides a benign and facile method to separate the final product after completion of the reaction by simply washing the crude mixture with common solvents such as hexanes to bypass expensive and time-consuming traditional methods such as column chromatography and recrystallization. 40 Many asymmetric reactions were successfully performed via GAP chemistry, including a Mannich-type reaction, 45 aza-MBH reaction, 46 Strecker reaction, 43 Umpolung reaction, 47 and the synthesis of peptides 48 among others. Recently, our group discovered a novel form of chirality, multi-layer 3D chirality, via GAP chemistry in which restriction of the free rotation of intramolecular layers generates chirality.…”
Section: Introductionmentioning
confidence: 99%